ASSESSMENT OF NON-FUNCTIONAL DISTRACTERS IN MULTIPLE CHOICE QUESTIONS: A DESCRIPTIVE ANALYSIS - Iqbal, Muhammad Zafar; Khan, Rehan Ahmed; Razaq, Nadeem (Pakistan Journal of Physiology, 2016)
Background: The ability of an examination to elicit cognition can be find out by systematic review of assessment scores of MCQs through item analysis. It is paramount to assess different parameters of MCQs which affect the quality of test items and eventually the standard of the assessment. Present research was focused to assess non-functional distracters of MCQs. Methods: Archival data of Item-analysis was used to assess the proportion of non-functioning distracters in the professional examination MCQ items attempted by undergraduate medical students. A total of 943 MCQ items were reviewed, including 4715 options (3772 distracters and 943 correct responses). Options which were opted by less than 5% of the total respondents were called as Non-Functional Distracters. Results: It was found that 943 MCQ items under study had 3772 distracters in total out of which 1742 (47.16%) were non-functional. It was seen that 162 items had 0, 239 had 1, 248 had 2, 169 had 3 and 125 items had 4 NFDs. Conclusion: High number of non-functional distracters showed that most of the options were used as fillers due to the lack of the faculty training program and less understanding of constructing MCQs. It is essential to make plausible distracters in a scientific manner rather than selecting them randomly as a filler for the questions. Pak J Physiol 2016;12(2):47–9